Differential effects of ‘resurrecting' Csp pseudoproteases during Clostridioides difficile spore germination - Donnelly, M. Lauren (Biochem J, 2020)
Clostridioides difficile is a spore-forming bacterial pathogen that is the leading cause of hospital-acquired gastroenteritis. C. difficile infections begin when its spore form germinates in the gut upon sensing bile acids. These germinants induce a proteolytic signaling cascade controlled by three members of the subtilisin-like serine protease family, CspA, CspB, and CspC. Notably, even though CspC and CspA are both pseudoproteases, they are nevertheless required to sense germinants and activate the protease, CspB. Thus, CspC and CspA are part of a growing list of pseudoenzymes that play important roles in regulating cellular processes. However, despite their importance, the structural properties of pseudoenzymes that allow them to function as regulators remain poorly understood. Our recently solved crystal structure of CspC revealed that its pseudoactive site residues align closely with the catalytic triad of CspB, suggesting that it might be possible to ‘resurrect' the ancestral protease activity of the CspC and CspA pseudoproteases. Here, we demonstrate that restoring the catalytic triad to these pseudoproteases fails to resurrect their protease activity. We further show that the pseudoactive site substitutions differentially affect the stability and function of the CspC and CspA pseudoproteases: the substitutions destabilized CspC and impaired spore germination without affecting CspA stability or function. Thus, our results surprisingly reveal that the presence of a catalytic triad does not necessarily predict protease activity. Since homologs of C. difficile CspA occasionally carry an intact catalytic triad, our results indicate that bioinformatic predictions of enzyme activity may underestimate pseudoenzymes in rare cases.